Morphological and molecular analysis of Henneguya tietensis n. sp. (Cnidaria: Myxosporea), parasitizing the gill filaments of Prochilodus lineatus (Valenciennes, 1837) from Brazil - Vieira, Diego Henrique Mirandola Dias [UNESP] (2021)
The present study describes Henneguya tietensis n. sp. parasitizing Prochilodus lineatus (Valenciennes, 1837) from Brazil, through morphological and molecular analysis. Myxospores were found in the gill tissue of P. lineatus with a prevalence of 10%. The myxospores consisted of two elongate, elliptical shell valves each with a long, tapering caudal appendage. The morphology was consistent with Henneguya and the myxospore measured as follows (mean ± SD): total length 55.5 ± 2.1 μm, body length 16.2 ± 1.1 μm, body width 5.5 ± 0.1 μm, caudal appendages length 39.0 ± 2.0 μm. The polar capsules were 7.3 ± 0.2 μm long, 1.7 ± 0.2 μm wide and contained a polar filament coiled 11 to 13 turns. Histological analysis showed the plasmodia developing in the middle region of each gill filament and caused a focally extensive distension by forming a space-occupying mass within the gill filament. The ultrastructural analysis allowed the observation of the presence of mature myxospores throughout the plasmodium. Phylogenetic analysis with the SSU rDNA gene showed Henneguya tietensis n. sp. as a sister species of the subclade formed by Henneguya piaractus and Henneguya brachypomus that infect fishes of the genus Piaractus. The genetically closest species was H. piaractus, which showed a similarity of 82.4%. Using molecular and morphological characterization, the myxozoan parasite described herein represents a new species of the genus Henneguya.